Analysis of Service Quality on the Starbucks Indonesia Application Using E-SERVQUAL and Importance Performance Analysis (IPA) - Palmarosa Ardianti Putri Hardhika; Minto Waluyo (Universitas KH. Abdul Chalim Mojokerto, 2025)
The advancement of technology has had a significant impact on various aspects of life, especially in terms of people’s dependence on digital services. This trend has driven e-commerce growth, especially in the food and beverage sector, including Starbucks Indonesia which offers a mobile application for enhanced customer experiences. Despites its popularity, the application has received a low rating of 2,4/5 on Google Play Store. This study aims to evaluate the app’s service quality using E-ServQual method, which assesses seven dimensions: efficiency, reliability, fulfillment, privacy, responsiveness, compensation, and contact. Additionally, Importance Performance Analysis is applied to identify critical performance factors requiring improvement. Data is collected through online surveys targeting users who have transacted via the app at least once. The result indicated that, 10 out of 19 service quality attributes exhibited negative gap values, indicating that user perceptions fell short of expectations in key areas such as responsiveness and privacy. These attributes were concentrated in Quadrant I of the IPA diagram. The study calculated an overall service quality level of 88% which, while relatively high, remains below the ideal 100% benchmark. This suggests notable gaps in meeting user needs, particularly when compared to industry standards for similar apps. Highlighting the need to prioritize service quality improvements across these 10 attributes to enhance the App’s service quality and meet user expectations. The study provides actionable recommendations for Starbucks Indonesia to prioritize service quality enhancements based on user feedback and performance analysis.